Response of Soybean to Early-Season Planting Dates along the Upper Texas Gulf Coast - W. James Grichar; Stephen P. Biles (International Journal of Agronomy)
Soybeans (Glycine max L.) can be planted along the upper Texas Gulf Coast from mid-March through May to take advantage of early season rains and to complete harvest before hurricane season and fall rains become a problem. However, in the Calhoun County area (28.5° north latitude), these planting dates have resulted in below average yields and reasons for these yield reductions are not clear. To determine if earlier planting dates could be an option to eliminate the low yields, field studies were conducted from 2005 through 2010 in Calhoun County, Texas, to determine soybean cultivar response to planting dates which ranged from mid-February through the last of April. Typically, soil temperatures in this area are above 18°C in mid-February and depending on weather patterns may not fall much lower during any time in the early portion of the growing season. The greatest yield was obtained with the mid-February and mid-March planting dates compared with early- or late-April planting dates. Typically, as planting date was delayed, the interval between planting and harvest decreased.